Contemporary Military Innovation : Between anticipation and adaption. - Adamsky, Dima (Cass military studies., 2012)
This book explores contemporary military innovation, with a particular focus on the balance between anticipation and adaption. The volume examines contemporary military thought and the doctrine that evolved around the thesis of a transformation in the character of war. Known as the Information-Technology Revolution in Military Affairs (IT-RMA), this innovation served as an intellectual foundation for the US defence transformation from the 1990s onwards. Since the mid-1990s, professional ideas generated within the American defence milieu have been further disseminated to military communities ac.